Evodiamine Augments NLRP3 Inflammasome Activation and Anti-bacterial Responses Through Inducing α-Tubulin Acetylation - Li, Chen-Guang; Zeng, Qiong-Zhen; Chen, Ming-Ye; Xu, Li-Hui; Zhang, Cheng-Cheng; Mai, Feng-Yi; Zeng, Chen-Ying; He, Xian-Hui; Ouyang, Dong-Yun (Frontiers in Pharmacology, 2019)
Evodiamine is a major ingredient of the plant Evodia rutaecarpa, which has long been used for treating infection-related diseases including diarrhea, beriberi and oral ulcer, but the underlying mechanism is unclear. Here we aimed to explore whether evodiamine influenced NLRP3 (NLR family, pyrin containing domain 3) inﬂammasome activation in macrophages, which is a critical mechanism for defending the host against pathogenic infections. We uncovered that evodiamine dose-dependently enhanced NLRP3 inﬂammasome activation in lipopolysaccharide-primed macrophages, as indicated by increased interleukin (IL)-1β production and caspase-1 cleavage, accompanied by increased ASC speck formation and pyroptosis. Mechanistically, evodiamine induced acetylation of α-tubulin around the microtubule organization center (indicated by γ-tubulin) in lipopolysaccharide-primed macrophages. Such evodiamine-mediated increases in NLRP3 activation and pyroptosis were attenuated by activators of α-tubulin deacetylase, resveratrol and NAD+, or dynein-specific inhibitor ciliobrevin A. Small interfering RNA knockdown of αTAT1 (the gene encoding α-tubulin N-acetyltransferase) expression, which reduced α-tubulin acetylation, also diminished evodiamine-mediated augmentation of NLRP3 activation and pyroptosis. Evodiamine also enhanced NLRP3-mediated production of IL-1β and neutrophil recruitment in vivo. Moreover, evodiamine administration evidently improved survival of mice with lethal bacterial infection, accompanied by increased production of IL-1β and interferon-γ, decreased bacterial load, and dampened liver inflammation. Resveratrol treatment reversed evodiamine-induced increases of IL-1β and interferon-γ, and decreased bacterial clearance in mice. Collectively, our results indicated that evodiamine augmented the NLRP3 inflammasome activation through inducing α-tubulin acetylation, thereby conferring intensified the innate immunity against bacterial infection.